Thermo-/photo-catalysts for aerobic oxidative cyanation of diverse oxygen-containing feedstocks - He, Jie; Zhou, Peng; Zhang, Shiying; Lam, Jason Chun-Ho; Liao, Yuhe; Zhang, Zehui (Green chemistry : an international journal and green chemistry resource : GC, 2024)
Nitriles constitute essential components in a vast array of both bulk and fine chemicals, as well as in various bioactive molecules. The aerobic oxidative cyanation of diverse oxygen-containing feedstocks, including alcohols, aldehydes, and ketones, stands out as a green and highly promising avenue for nitrile synthesis over both thermocatalysts and photocatalysts. In this review, we initially elucidate the reaction mechanisms involved in the oxidative cyanation of oxygen-containing compounds. Following this, we present a summary and commentary on the predominantly achieved progress in the oxidative cyanation of various oxygen-containing feedstocks over the last decade. The categorization is based on types of catalysts, including non-noble metal catalysts, single-metal-atom catalysts, metal-free catalysts, and photocatalysts. Additionally, we assess the current catalytic systems from the standpoint of green chemistry. Finally, we conclude by highlighting the current challenges and delineating our prospects for future research endeavors. Aerobic oxidative cyanation of diverse oxygen-containing compounds over thermo- and photocatalysts is highlighted as a green and promising avenue for nitrile synthesis.